Estación de servicio en la zona urbana
La obra se ubica en Álvarez Thomas 401, esquina Maure, Buenos Aires.
Keywords: GROSMAN, MARCOS; ARGENTINA; BUENOS AIRES (PROV); BUENOS AIRES; ESTACIONES DE SERVICIO